The improvement of external transport cost evaluation in the context of Lithuania’s integration into the european union - Išoraitė, Margarita (Transport, 2003)
The accepted accession to the European Union in Lithuanian internal transportation is regulated by the coordination of national legal acts with the international conventions arid documents of various international organisations. This process was particularly accelerated when Lithuania started negotiations on the accession to the European Union. Future transport pricing policy of Lithuania has two objectives – to guarantee the covering of operational costs and to strive for economic efficiency. These objectives should not be coincident. Economic, institutional and legal refonns in Lithuania are implemented with the aim to co-ordinate the standards and regulations effective in Lithuania with the acts of the European Union. In the article on the basis of pricing of the peak, the social marginal, the environmental costs referring to the advanced research of Western and US scientists, were analysed and improved the evaluation of external Lithuanian transport costs and economic methods enabling the integration of external transport costs into the internal costs were offered. The improvement of external cost evaluation will enable the integration of external transport costs in line with the EU standards. One of the most actual problems of Lithuania is the growth of environmental impact and social subsequences caused by the increase of transport in Lithuania: Increasing traffic jams, air pollution, growing rates of accidents and noise emission are the main problems of the Lithuanian transport system. Thus, in transport system, besides the internal costs, there exist the external costs that are not reflected in transport cost price. These costs are caused by air pollution, worsened health condition of people, decreased agrarian fertility, increased water pollution, etc. Therefore it is necessary to evaluate these external transport costs and to propose the ways of their reduction as well as their inclusion into the transportation price. The methodological basis of the article is the method of systematic and multicriteria! analysis aiming at the evaluation of the necessity of the inclusion of external transport costs into the transport price with the attitude towards the national and the carrier’s positions. Research work of Western and US scientists was referred to the grounding of the necessity of external transport costs in Lithuania. Having analysed the experience of the scientists of US and Western countries, as well as the practice of Lithuanian scientists, a methodology for the evaluation of external transport costs in the country was offered. The application of the EU standards is tackled as well. Most ideas suggested in the article could be valuable for further formation and enhancement of external costs of economic technique in Lithuania thus approaching the national pricing to the EU standard system. The evaluation made in the article shall be applied for the implementation of external transport cost evaluation technique in Lithuanian transport. First Published Online: 19 Dec 2011